97.7k views
4 votes
Y=–3x + 6y=9 What is the solution to the system of equations? (–21, 9) (9, –21) (–1, 9) (9, –1)

User ComeIn
by
5.3k points

1 Answer

4 votes

ANSWER


The solution is
(-1,9)

Step-by-step explanation

We want to solve the simultaneous equations



y=-3x+6---(1)


and



y=9--(2).


We substitute equation (2) in to equation (1), to obtain



9=-3x+6


This has now become a linear equation in a single variable
x.


We solve for x by grouping like terms.



9-6=-3x



3=-3x


We divide through by negative 3 to get;



-1=x.


Hence, the solution is
(-1,9)





User Rafael Zottesso
by
5.5k points